FIELD RESEARCH ON PASTURE VEGETATION IN SOUTH UZBEKISTAN (IN KASHKADARYA REGION PARTS) - Uktam Khujanazarov; Gulrukhsor Ergasheva; Gulbakhor Akbarova (The Bioscan, 2024)
This paper involves the practical use of pastures in the Kashkadarya region. Therefore, the data on cartographic and monitoring fodder yield were given. To determine the fodder productivity of the foothill pastures during the year in the spring is carried out in the fieldwork through principled methodological schemes: drawing up a pasture card as a standard describing the average productivity indicators of many years; carrying out surface field inspections for control in the most important grazing areas; annual inspections for the use of pastures as fodder and grazing of livestock.